Implementação do sistema lean manufacturing em uma indústria de vidros temperados do Paraná - Garcia, João Felipe Cadore (2022)
Currently, market competitiveness and innovation concern and challenge managers, bringing attention to metrics such as quality and productivity. With this, Lean Manufacturing becomes an attractive option because from it, it is possible to improve these two aspects of a production process. Seeking these improvements, this work seeks to apply the Lean Manufacturing production system in a tempered glass industry in Paraná, seeking improvements in lead time and production volume, as well as the reduction of the non-conformity rate. To this end, action research was used as a methodology in the application of several Lean principles, such as just-in-time, kanban, continuous flow, heijunka, among others. From the results obtained, it was found that revenue (per square meter) increased by 42%, production lead time was reduced by 17%, the conversion rate of raw material into finished product increased by 43%, and the amount of one of the major non-conformities was reduced by 75%, results achieved without changes in the company's work regime, proving the effectiveness of Lean Manufacturing.